Organotin(IV) trifluoromethanesulfonate chemistry: isolation and characterization of novel 1,10-phenanthroline-based derivatives - Cattey, Hélène; Plasseraud, Laurent (Comptes Rendus. Chimie)
The reactivity of the hydroxo di-n-butyltin trifluoromethanesulfonato dimer complex [n-Bu2Sn(µ-OH)(H2O)(CF3SO3)]2 (1) toward 1,10-phenanthroline (phen) has been investigated, leading to the formation of two novel di-n-butyltin(IV) trifluoromethanesulfonate complexes [n-Bu2Sn(µ-OH)(phen)]2[CF3SO3]2 (5) and [n-Bu2Sn(phen)2][CF3SO3]2 (6), in which the tin atoms are bis-chelated by one and two bidentate phen ligands, respectively. Salts 5 and 6 were characterized by single crystal X-ray diffraction analysis, elemental analysis, mass spectrometry, and infrared spectroscopy as well as 1H, 19F, 13C{1H}, and 119Sn{1H} NMR spectroscopy. Monitoring by 119Sn{1H} NMR spectroscopy in CD3CN solution of the reaction proceeding with successive addition of phen revealed the in situ formation of three organotin(IV) trifluoromethanesulfonate intermediate species. Two of these, namely {[n-Bu2Sn(H2O)]2O·n-Bu2Sn(OH)2}[CF3SO3]2 (2) and [n-Bu2Sn2(OH)(CF3SO3)]2O (4), were already known and could be clearly identified on the basis of their 119Sn{119H} NMR chemical shifts. The composition of the third intermediate, 3, with an unknown chemical shift value, was investigated. A possible structure, especially suggested by electrospray-ionization mass spectrometry, is proposed as [{n-Bu2Sn(phen)(CF3SO3)}2(µ-CF3SO3)][CF3SO3]. Furthermore, from a mixture of 1 and phen in equimolar ratio, in dichloromethane solvent and at –20 °C, temperature-sensitive crystals of a new hydrated di-n-butyltin cation, [n-Bu2Sn(phen)(OH)(H2O)][CF3SO3] (7), were isolated. Crystals of the organic salt 1,10-phenanthrolinium trifluoromethanesulfonate (phenHOTf) were also obtained from the filtrate of the mother-liquor. The reactivity of 1 toward 2,9-dimethyl-1,10-phenanthroline was also explored (dmphen), leading to the detection of characteristic fingerprints of distannoxanes 2 and 4 by 119Sn{119H} NMR, and to the crystallization of phenanthrolinium triflate salts, which were characterized by X-ray diffraction analysis as dmphenHOTf and dmphenHOTf·dmphen.